2009 International Conference on Computer Technology and Development 2009
DOI: 10.1109/icctd.2009.213
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Intrauterine Growth Retardation Using Fetal Abdominal Circumference

Abstract: An enhanced method for automatically extracting the fetal Abdominal Circumference (AC) using the Gradient Vector Field (GVF) snake is presented in this paper. Speckle Reducing Anisotropic Diffusion (SRAD) filter has been used for speckle suppression. The Iterative Randomized Hough Transform has been applied to the image to find the initial contour of fetus abdomen. Finally, the GVF snake adapts the initial contour to the real edges of the abdominal contour. The measured AC has been used to determine the Intrau… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 12 publications
0
5
0
Order By: Relevance
“…1(a) and (b)]. However, the task of segmenting the abdomen is more challenging and only few works have attempted it up-to-date [14], [20], [21]. General methods retrieving all standard fetal biometric measurements used in antenatal clinical practice are limited [22], [23], [4], [24].…”
Section: Introductionmentioning
confidence: 99%
“…1(a) and (b)]. However, the task of segmenting the abdomen is more challenging and only few works have attempted it up-to-date [14], [20], [21]. General methods retrieving all standard fetal biometric measurements used in antenatal clinical practice are limited [22], [23], [4], [24].…”
Section: Introductionmentioning
confidence: 99%
“…The image gradient-based method showed stable performance for high-contrast HC and FL environments, which AC measurements were considered more challenging because fetal abdomen had low environmental contrast, non-uniform contrast, and irregular shape on ultrasound images. Therefore, among biometric measurements, AC was the most predictive of fetal weight, whereas variations in AC measurements led to significant differences in EFW [7]. Abdella et al in their study also found that AC can be used as a single marker in diagnosing macrosomia [8].…”
Section: Introductionmentioning
confidence: 90%
“…After applying the above method, the fetal weight is estimated using the abdominal circumference; the comparison between the accuracy of the automatic and manual measurements were presented [ 53 ]. Further, a GVF snake is reported by Nithya and Madheswaran [ 54 ] to form or extract the contour of the abdominal circumference. The value of the abdominal circumference is used to detect the intrauterine growth retarded (IUGR) fetus.…”
Section: Extraction Of Fetal Parameters By Segmentation Techniquesmentioning
confidence: 99%